DEVELOPING LANGUAGE ASPECTS IN MENTIONING LETTER SYMBOLS IN GROUP B OF NURUTTAQWA KINDERGARTEN BANJARMASIN - setyana Oktavia; Akhmad Riandy Agusta (E-CHIEF Journal, 2023)
This research was motivated  by the lack of development  of  children's  ability to mention letter symbols caused by the  media used by  teachers in the learning process  to recognize letters that did not attract children's hearts, thus making children less enthusiastic and not eager to participate in learning activities.  The purpose of this study is to improve and improve the quality of the learning process of group B in Nuruttaqwa Kindergarten Banjarmasin.  This research approach uses qualitative and quantitative approaches  with the type of classroom action research (PTK) held 4 meetings. Techniques for collecting observations of teacher activities, observation of children's activities, children's learning outcomes, language skills.   The results showed that teacher activity increased with a score of 25 criteria "Very Good" at meeting 4. Children's activity at each meeting increased with a percentage of 84.62% of the criteria being very active at meeting 4. Children's language development with a percentage of 92.31% or 30 children successfully developed at meeting 4.